EKSISTENSI RITUAL MELAUT DI PUSARAN PAHAM KEAGAMAAN - Erens Elvianus Koodoh (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2020)
Going to sea is a must for fishermen to survive. On the one hand, going to sea guarantees economic survival and income sustainability. But on the other hand, fishermen are also faced with uncertainty at sea, because at sea many unexpected things can happen that can be life threatening. This uncertainty in the sea brings fishermen to a basic human instinct, which is trying to survive by minimizing and anticipating bad things that might happen while at sea. Fishermen are aware of their weaknesses and have high hopes for the protection of the ruler of nature, the Almighty. From this awareness, the ritual begins, namely the ritual or worship of the Almighty so that in addition to avoiding reinforcements, fishermen also hope to get sufficient results or even more as a gift from the Almighty. Sea-related rituals are very common in coastal areas and small islands in Southeast Sulawesi. As time goes by, technological developments and the spread of religious understanding, some people consider the rituals carried out by fishermen to be shirk behavior that doubles God so that it must be eliminated and return to the purity of religious teachings. Interviews and field observations are methods used in obtaining data. The findings of this study indicate that with the increase in religious understandings that tend to be "tough" on the ritual traditions of the sea, there is a conflict between the understanding of the ingrained traditional practice and religious understanding which tends to reject the cultural practices of the local community. In the end, the fishermen slowly left the tradition. In practice, the tradition of going to sea is considered AS a form of shirk. Some people and also religious groups reject the existence of the ritual tradition of fishing.